ANALISIS TINGKAT KERUSAKAN RUAS JALAN DAN SOLUSI PENANGANANNYA PADA RUAS JALAN SAWAH LUNTO, KOTA SAWAH LUNTO - Honesti, Leli; Yusnita, Yessy; Alhaadi, Ryan Eko (Rang Teknik Journal, 2024)
The Sawahlunto Road section is a connecting road between Sawahlunto City and Tanah Datar Regency, where a lot of vehicles pass through this road so the road damage that occurs on this road section results in the structural and functional condition of the road being no longer able to provide optimal service. Therefore, this research aims to analyze the damage to flexible pavement using the Pavement Condition Index (PCI) method on the  Sawahlunto Street, from   Sta 2+000 to Sta 3+200, precisely from Simpang Kolok Mudik Street  to the Sawahlunto Triangle Square. The data used is primary data, namely data obtained from field surveys in the form of documentation of width, length, and depth of road damage, while secondary data is a map of the research location taken via the Google Earth application. Based on the research results, there are 7 types of damage and the percentage of damage on the road includes potholes at 1.124%, subsidence damage at 43.33%, patch damage at 6.098%, granular release damage at 46.670%, fine crack damage at 1.204%, crack damage. crocodile skin was 0.449%, edge crack damage was 1.123%. Hence, with a total length of the Sawahlunto Road section of 1.2 km, the road damage index value obtained using the PCI method was 53, falling into the range (41-55) with the Fair damage category. Because this road is one of the access roads between Sawahlunto City and Tanah Datar Regency, it can be recommended to replace this road section with composite pavement (a combination of flexible and rigid pavement) because composite pavement has higher lower structural strength and the top layer uses flexible pavement to provide comfort for motorists who use this road.